Perbedaan Gaya Kepemimpinan Di Sekolah Yang Bagus Dan Kurang Bagus - Nurbulan, Eka; Silalahi, Yulianda Ghrace; Winara, Winara; Lubis, Wildansyah (CV. Pusdikra Mitra Jaya, 2024)
This article discusses a comparison of leadership in the context of good and less good schools. Leadership in educational institutions is very important for achieving academic goals and developing student character. However, leadership at elementary school A and elementary school B has differences in leadership style. This study uses a qualitative approach with data collection techniques through in-depth interviews with school leaders at SDN A and SDN B. Data analysis was carried out using the thematic analysis method. The results of the research show that leadership in SDN A schools is more focused on achieving educational goals, while leadership in SDN B schools, on the other hand, is not focused on achieving academic or other targets. In the context of educational development in Indonesia, this research can provide insight and understanding of the differences in leadership in two different schools. The conclusion of this research is that as a leader it is important to understand and adapt leadership styles to achieve mutual success in accordance with national education goals. In implementing research results, leadership training programs to improve quality, increase communication and collaboration, improve resource management systems, and increase innovation and creativity can be carried out as concrete steps to improve the quality of leadership in schools. It is hoped that the results of this research can provide guidance for educational leaders in improving the quality of leadership and educational development in Indonesia in accordance with national education goals.